Efeitos da substituição da dieta hiperlipídica pela dieta padrão sobre a homeostase glicêmica e esteatose hepática em camundongos - Melo, Vanessa Cristina de Souza (2024)
The consumption of ultra-processed foods, high in fat, has contributed to the global increase in obesity and other metabolic disorders resulting from excess adipose tissue, including Non-Alcoholic Fatty Liver Disease. Physical exercise and dietary reeducation constitute first-line treatment for weight loss; however, in an attempt to accelerate weight loss, the use of restrictive diets is common, which are unsustainable in the long term and result in weight regain. Objective: To investigate whether replacing a high fat diet with a normolipidic (standard), non-restrictive diet can contribute to improving body composition, glycemic homeostasis, and hepatic steatosis in obese mice fed a high-fat diet. Methods: In the first phase, the animals were divided into two groups, one receiving a high-fat diet and the other a standard diet, for 8 weeks. In the second phase, half of the animals on the high-fat diet had their food replaced with a standard diet. Body weight was measured weekly, and tests were performed to assess food intake and glucose and insulin tolerance. The animals were euthanized after 8 weeks of dietary intervention, and a fragment of liver tissue was extracted for histological analysis. Results: The high-fat diet induced obesity, with substantial weight gain, and metabolic alterations, such as hyperglycemia, insulin resistance, dyslipidemia, and hepatic steatosis. On the other hand, replacing it with a standard diet did not influence total daily caloric intake, but food consumption during the daytime was lower in the group fed the standard diet. Furthermore, dietary intervention restored body weight, normalized blood glucose, lipid profile, and minimized hepatic steatosis. Conclusion: Less restrictive dietary interventions, based on balanced macronutrient diets, are effective in treating obesity and comorbidities.